Developments in Plasma Arc Cutting (PAC) of steel alloys: a review - Cinar, Zeki; Asmael, Mohammed; Zeeshan, Qasim (Penerbit Universiti Kebangsaan Malaysia, 2018)
The Plasma Arc Cutting (PAC) process was developed for difficult-to-machine materials in order to overcome the inefficiency and ineffectiveness of conventional machining methods when it comes to complex shapes and tool wear due to the contact between the tool and the workpiece. PAC consumes ionized gas, known as the heat source, and a high energy stream, known as the plasma. Many researchers have examined the PAC of steel alloys by considering the cutting power, scanning speed, cutting height and plasma gas pressure as the process parameters, and analysing the effects on the edge roughness, the kerf taper angle (conicity), burr formation, Heat Affected Zone (HAZ), Material Removal Rate (MRR), surface quality after cutting, and the metallurgical effects of the cut. A comprehensive review was carried out on developments in the analysis and optimization of PAC for steel alloys. It is observed that, the feed rate and edge roughness have a significant effect on the machining characteristics; however, less consideration was given by the researcher to these parameters. In addition, a critical comparison was made of the process parameters involved and the methods of analysis used, with the aim of providing the status of current research and guidance for future research.